2001
DOI: 10.1530/eje.0.1440237
|View full text |Cite
|
Sign up to set email alerts
|

IGFs and IGF-binding proteins in short children with steroid-dependent nephrotic syndrome on chronic glucocorticoids: changes with 1 year exogenous GH

Abstract: Objective: Children with steroid-dependent nephrotic syndrome (SDNS), despite being in remission on glucocorticoids, continue to have growth retardation and short stature. The mechanism is uncertain as both chronic glucocorticosteroids and the nephrotic syndrome may independently affect growth. We investigated the changes in the IGFs and IGF-binding proteins (IGFBPs) in a group of short SDNS children, and studied the changes prospectively with 1 year's treatment with GH. Design and Methods: Total and`free' IGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
1
14
0
2
Order By: Relevance
“…The reduction in serum IGF-1 could indicate amelioration of an IGF-1 signaling defect in skeletal muscle (10,26). Alternatively, the increase in IGFBP-1 could stimulate IGF-1 action at the cellular level, despite lower serum IGF-1 (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in serum IGF-1 could indicate amelioration of an IGF-1 signaling defect in skeletal muscle (10,26). Alternatively, the increase in IGFBP-1 could stimulate IGF-1 action at the cellular level, despite lower serum IGF-1 (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with steroid-dependent NS, growth hormone treatment has been found to increase the level of insulin like growth factor-1 (32). In the literature, it was reported that an adolescent patient with short stature who was diagnosed with steroid-dependent NS was treated successfully with recombinant human growth hormone during usage of cyclosporine (33).…”
Section: Discussionmentioning
confidence: 99%
“…However, this is in line with earlier reports describing an association between glucocorticoid use and increased serum IGF-1. (41)(42)(43)(44)(45) The IGF-1-related detrimental effects of glucocorticoid treatment on bone therefore rather may be the result of IGF-1 resistance and/or reduced local IGF-1 expression in osteoblasts. (41,42,(44)(45)(46)(47) Adjustment for glucocorticoid treatment did not alter the association between low serum IGF-1 and increased risk of fractures observed in this study.…”
Section: Discussionmentioning
confidence: 99%